The Anthropology of Security Perspectives from the Frontline of Policing, Counter-terrorism and Border Control - Maguire, Mark; Frois, Catarina; Zurawski, Nils (Pluto Press, 2014)
In a post-Cold War world of political unease and economic crisis, processes of securitisation are transforming nation-states, their citizens and non-citizens in profound ways. The book shows how contemporary Europe is now home to a vast security industry which uses biometric identification systems, CCTV and quasi-military techniques to police migrants and disadvantaged neighbourhoods. This is the first collection of anthropological studies of security with a particular but not exclusive emphasis on Europe. The Anthropology of Security draws together studies on the lived experiences of security and policing from the perspective of those most affected in their everyday lives. The anthropological perspectives in this volume stretch from the frontlines of policing and counter-terrorism to border control.